2019
DOI: 10.1177/0192513x19831410
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Health Lifestyles in Families Experiencing Disability

Abstract: The family system is an important contributor to one's development of health lifestyles or the patterns of health behaviors one engages in. Research has yet to explore how health lifestyles develop within families or how disability may affect this process. This study uses qualitative data collected from parents and key informants in two U.S. communities to address this gap in the literature. Findings capture a process through which health lifestyles develop in families with a child with a disability. This proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Estos resultados pueden explicarse según la teoría, ya que ser cuidador informal en contexto de discapacidad puede incrementar los niveles de resiliencia porque los cuidadores se tornan más conscientes de la importancia del https://doi.org/10. 16888/interd.2023.40.3.13 Calidad de vida y funcionamiento ejecutivo mantenimiento de su salud mental (Brito et al, 2022;Pinquart y Sörensen, 2003;Rigles, 2019). Así también, es importante considerar que la mayoría de los participantes de este estudio contaba con apoyo institucional y apoyo externo para el cuidado del niño o adolescente.…”
Section: Discussionunclassified
“…Estos resultados pueden explicarse según la teoría, ya que ser cuidador informal en contexto de discapacidad puede incrementar los niveles de resiliencia porque los cuidadores se tornan más conscientes de la importancia del https://doi.org/10. 16888/interd.2023.40.3.13 Calidad de vida y funcionamiento ejecutivo mantenimiento de su salud mental (Brito et al, 2022;Pinquart y Sörensen, 2003;Rigles, 2019). Así también, es importante considerar que la mayoría de los participantes de este estudio contaba con apoyo institucional y apoyo externo para el cuidado del niño o adolescente.…”
Section: Discussionunclassified
“…We also note an exception to participants' predominant pattern of using privilege to justify de-emphasizing physical or psychological health. This exception involved families who included someone with a disability or serious health condition (Rigles, 2019). Parents in these families explained that they could not take physical or psychological health for granted and thus could not spend the "currency" of good physical health in de-emphasizing some aspects of it, despite their advantaged positions.…”
Section: Discussionmentioning
confidence: 99%
“…Bolstering her identity as a good parent around health, Jessica focused in the interview on her efforts to provide a good diet, "cook everything from scratch," and emphasize good sleep. Jessica had a child with a serious health condition, so her focus on bolstering physical health was expected (Rigles, 2019). Other class-privileged parents' narratives showed that when child health concerns were absent, they were able to use their children's current health and their high-resource lives as a currency of sorts.…”
Section: Justifying Parenting Priorities and Choices For Children's H...mentioning
confidence: 99%
“…Scientists have determined that people who are left excluded from society due to their special needs are more affected by stress, which negatively influences also the health and behavior of their family members (Rigles, 2019). A margin between active society and vulnerable social groups is ever increased in the time of the pandemic (Dukes & Berlingo, 2020).…”
Section: Social Exclusion During the Covid-19 Quarantinementioning
confidence: 99%